Analysis of the Influence of Profitability, Agency Costs, and the Composition of the Independent Commissioners on Financial Distress - M Yusril Hasani; Siti Atikah; Indria Puspitasari Lenap (International Journal of Asian Business and Management, 2024)
This study aims to explain the influence of profitability, agency costs, and independent commissioners on financial distress in energy companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The analysis method in this research begins with collecting secondary data from the financial reports of energy companies sampled using purposive sampling techniques, with a total of 61 companies. Hypothesis testing was conducted using panel data regression methods with the EViews 13 software. The results of the study show that profitability proxied by ROA does not have a significant effect on financial distress, while agency costs have a positive and significant effect on financial distress. On the other hand, independent commissioners do not have a significant influence on financial distress. The implication of this research is that an increase in agency costs can be an indicator of financial distress risk in companies, so companies and investors are expected to pay more attention to the management of agency costs to reduce the potential for bankruptcy